Ductile damage variation analysis during metal extrusion process using design of experiment technique. (20th December 2005) - Hambli, Ridha; Lepadatu, Daniel; Kobi, Abdessamad; Barreau, Alain
In this work, the design of experiments method has been used for a better understanding of the influence of the deviation of the material parameters on the damage evolution within the workpiece. To predict the evolution of the material deterioration during the processes, a damage model accumulation has been implemented in a finite element code and applied with success to simulate damage and crack propagation, which can be generated by the plastic deformation during the operations. The simulation can predict forming defects such as crack initiation and propagation. The mechanical quality of a part is determined by the material property variation such as the hardening and damage states as a result of the increase in strain.